Digital natives: A case study exploring the digital literacy gaps in a Rural High School - Danao, Angeline B.; Enriquez, Michael Emmanuel; Montejo, Kurt Benedict; Patricio, Abraham; Sonido, Matthew Willdeo; Ador, Zohail (Goodwood Publishing, 2025)
Purpose: The main purpose of this study was to have an in-depth exploration of rural students' digital literacy in the 21st century. Research methodology: This research employed a case type of study, which explored the digital literacy of four (4) rural high school students in San Pablo City. Participants were selected through purposive sampling with researcher-made criteria. They were interviewed using a semi-structured interview via Google Meet. A thematic analysis was used to further understand their digital literacy. Results: Their digital literacy skills appeared to be needing improvements. Different factors were also mentioned to affect their digital literacy including their geographical locations, personal factors, and their limits to access the internet and the technology. However, they still incorporated help-seeking and self-studying to improve their digital literacy. Limitations: The students’ grade levels were not specified. Specific students with different grade levels could have different findings. Contribution: This research uncovered the challenges, skills, and solutions to problems that included the students' digital literacy in rural areas. This could be beneficial to students in a rural area as a basis for the improvement of their digital literacy.